Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

My question is: Represent the following set of points in the $\,xy\,$- plane:

$$\left\{ (x,y)\,\, |\,\, x^2 + y^2 - 2x - 2y + 1 = 0 \right\}$$

What i got: $\,\,(x-2)^2 + (y-2)^2 = 1\,\,$

I am not getting what to do next. Any help to solve this question would be greatly appreciated. Thank you,

share|cite|improve this question
I am not sure how you got $(x-2)^2$ in your solution - I think you need to look very carefully at the expansion of $(x-2)^2$ to see where you are going wrong. – Old John Jun 9 '12 at 21:47

When given an equation of the form $x^2-2x+y^2-2y+1=0$ the first step is to complete the square for $x$ and for $y$.

The idea is that if we have $x^2-2x$ we can write it as $(x+C)^2+D$ instead. Since know those that the coefficient of $x$ is $2C$, we know that $C=-1$, so we have: $$(x-1)^2=x^2-2x+1\implies x^2-2x = (x-1)^2-1$$

Therefore we can write it as $(x-1)^2-1$.

Similarly we can replace $y^2-2y$ by a similar term, so we have now:

$$\begin{align} &\underbrace{x^2-2x}+\underline{y^2-2y}+1 = 0 &&\text{complete the squares}\\ &\underbrace{(x-1)^2-1}+\underline{(y-1)^2-1}+1 =0 &&\text{sum the }1\text{'s}\\ &(x-1)^2+(y-1)^2-1=0 &&+1\\ &(x-1)^2+(y-1)^2=1 &&\text{ circle!} \end{align}$$

Therefore we have a circle of radius $1$ whose center is at $(1,1)$.

share|cite|improve this answer
This is how you do it without colors. – Asaf Karagila Jun 9 '12 at 23:26

Well it's a circle, I guess. Centre is $(1,1)$, radius is $1$.

If you want to draw it, you'll need this mighty instrument

share|cite|improve this answer

$$x^2+y^2-2x-2y+1=0\Longrightarrow (x-1)^2+(y-1)^2-2+1=0\Longrightarrow$$$$\Longrightarrow (x-1)^2+(y-1)^2=1$$Do you recognize it now?

Added In general we can complete the square as follows: $$ax^2+bx=a\left(x^2+\frac{b}{a}\right)=a\left(x+\frac{b}{2a}\right)^2-\frac{b^2}{4a}\,\,,\,\,a\neq 0$$

share|cite|improve this answer
yes,i got it! :) – mgh Jun 9 '12 at 21:51
@Meg Good! Just some corrections in your completing the squares, that's all. – DonAntonio Jun 9 '12 at 21:53

The first problem is that you carried out the algebra incorrectly. When you complete the square with $x^2-2x$ you should get $(x-1)^2-1$, which you can verify by multiplying it out. Similarly, $y^2-2y=(y-1)^2-1$. Thus, $$\begin{align*}x^2+y^2-2x-2y+1&=(x-1)^2-1+(y-1)^2-1+1\\ &=(x-1)^2+(y-1)^2-1\;, \end{align*}$$

and the points where $x^2+y^2-2x-2y+1=0$ are the points where $(x-1)^2+(y-1)^2-1$, i.e., where $(x-1)^2+(y-1)^2=1$.

What’s the distance between the points $(x,y)$ and $(1,1)$? It’s $\sqrt{(x-1)^2+(y-1)^2}$, right? And if $(x-1)^2+(y-1)^2=1$, then $\sqrt{(x-1)^2+(y-1)^2}=\sqrt1=1$, so your set contains the points whose distance from $(1,1)$ is $1$. What does that set of points look like?

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.